Pengaruh Model Pembelajaran Cooperative Learning Tipe Teams Games Tournament (TGT) terhadap Hasil Belajar Siswa di MI Tarbiyatul Falah Citeureup-Bogor - Nurul Aeni; Ahmad Syarif; Ernawati Ernawati (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2021)
This study aims to determine the effect of the Teams Games Tournament (TGT) cooperative learning method on science learning outcomes. The research method used was experimental and the data used were quantitative data. The subjects of this study were students of class VI MI Tarbiyatul Falah Citeureup Bogor. With a total of 30 students consisting of 18 boys and 12 girls. The results of the study were obtained using the Games Tournament (TGT) Cooperative Learning Model. The results of data analysis techniques using the t test formula on the pretest and posttest data. The results showed tcount = 17, 69 t table 2.04, thus Ho is rejected and Ha is accepted, which means that there is an effect of cooperative learning model on science learning outcomes.